Transient lupus anticoagulant: an unusual cause of bruising in children. Issue 5 (3rd September 2003) - Anderson, A-K; Mohan, U; Liesner, R
Abstract : A child presented with excessive bruising and prolonged activated partial thromboplastin time. Mixing studies in plasma were positive for phospholipid dependence of the anticoagulant, confirming a diagnosis of lupus anticoagulant. Factor II level was reduced. Laboratory findings normalised after three months, with spontaneous resolution of bruising. This case demonstrates a transient antiphospholipid antibody syndrome as a rare presentation of bleeding diathesis in a previously healthy child, and should be considered in children with new onset bruising and prolonged activated partial thromboplastin time.